Study on Isozymes from Aedes Aegypti Strains of some Residential Areas in Vietnam - Lien, Do Ngoc; Hoai, Nguyen Thi Thu; Huong, Vu Duc (VNU Journal of Science: Natural Sciences and Technology; Vol 19 No 4, 2003)
Abstract